PENGHEMATAN KONSUMSI LISTRIK PADA POS RONDA DI KOMPLEK MOLEK 1 KOTA BEKASI - Indah Suwartini, Dwi; Prayoga, Dedek; Mahdy Guna, Muhammad; Naufal Suherlan, Muhammad; Mauludin Nomba, Sya'ban; Lakoro, Syafrizal; Dwicky Adithya, Tsadan; Rama Insiyanda, Dita (Education and Talent Development Center of Indonesia, 2025)
This community service activity aims to educate residents of Komplek Molek 1, Bekasi City in managing energy consumption efficiently through the use of Smart WiFi Plug technology based on the Internet of Things (IoT). This activity was carried out with an experimental quantitative approach that compared electricity consumption at the guard post before and after using the device. The results of the observation showed a decrease in energy consumption from 0.21 kWh to 0.18 kWh per day, which means a savings of 0.9 kWh per month or Rp1,530. This technology allows automatic regulation of the lighting time, so that electricity use becomes more controlled and efficient. In addition to providing technical impacts, this activity also encourages energy literacy and active community participation in implementing appropriate technology in their residential environment. These findings prove that the implementation of simple technology-based solutions can be a real step in supporting energy efficiency at the community level.